Higher Teacher Education: Raising Awareness toward Constructing Teaching Philosophy Statements - Abdulghani Muthanna (Athens Institute for Education and Research, 2022)
This article focuses on exploring whether teacher educators and teacher students at higher teacher education programs have constructed their teaching philosophy statements, how they implement such philosophy statements, and how they develop and evaluate the contents of the teaching materials related to the courses they are instructing. By following the qualitative case study methodology, the author employed semi-structured interviews with twenty teacher educators and fifteen teacher students from one state higher education institution in Yemen. With the employment of thematic network analysis techniques, the findings report on the lack of awareness concerning the teaching philosophy statements construction, the random process of designing and evaluating teaching materials, and the lack of teaching aids for realizing the teaching philosophies of those with developed teaching statements. For practical implementation, university leaders and administrators are recommended to establish a program that focuses on the professional development of the teaching faculty with a focus on highlighting and providing useful knowledge on the 'teaching philosophy statements' construction and 'materials design and evaluation' processes.